PEMANFAATAN SISTEM PEMBANGKIT LISTRIK HYBRID UNTUK POMPA ALIRAN NUTRISI INSTALASI HIDROPONIK - Pulungan, Ali Basrah; Sidiqi, Adam Rasyid; Hamdani, Hamdani; Purwantono, Purwantono (Universitas Mataram, 2024)
The hydroponic installation in the hydroponic community of Matur District, Agam Regency, West Sumatra, faces a major problem with a crop failure rate reaching 30%-35%. This issue is primarily caused by disruptions in nutrient flow due to the lack of continuous electricity, which affects pump operation. To address this problem, efforts are needed to ensure that the nutrient flow to the plants is maintained. The aim of this activity is to assist the hydroponic community in increasing plant production through the application of innovative technology. The solution implemented is the use of hybrid power generation system technology, integrating Solar Power Plants (PLTS) and PLN electricity. This system ensures that water pumps operate optimally, even at night or during bad weather. The implementation of this technology has been completed and directly tested. The pump is capable of delivering nutrients to all planting holes. The performance testing of the hybrid power generation system was conducted in the laboratory and at partner locations. The results of the system testing show that the voltage values meet the load requirements, with a voltage difference still within the tolerance range of 2.2% - 3.3%, thus not disrupting the motor's performance. The energy source switching time is <4 seconds, specifically 0.6 seconds from the solar power plant (PLTS) to the national grid (PLN) and 3.4 seconds in the opposite direction. This transition indicates that the hybrid power generation system operates efficiently, with pumps and lighting functioning well. Thus, it is expected that this system can significantly increase the productivity of hydroponic plants and boost the income of the hydroponic community.